Patient and prescriber characteristics among patients with type 2 diabetes mellitus continuing or discontinuing sulfonylureas following insulin initiation: data from a large commercial database. (3rd June 2018) - Beachler, Daniel C.; Fernandes, Gail; Deshpande, Gaurav; Jemison, Jamileh; Lyons, Jennifer G.; Lanes, Stephan; Liu, Jinan; McNeill, Annie
Abstract: Objective: To describe patient and provider characteristics for patients with type 2 diabetes (T2DM) initiating basal insulin and describe basal insulin's impact on sulfonylurea (SU) discontinuation. Methods: A retrospective cohort study was conducted using the HealthCore Integrated Research Database. Patients had ≥12 months of continuous coverage prior to initiating insulin, and were utilizing at least one anti-hyperglycemic drug at the time of insulin initiation. Predictors for SU discontinuation were evaluated utilizing Cox proportional hazards models. Results: Among the 74, 334 individuals aged ≥18 years with T2DM who initiated basal insulin from 2006–2015, 30% were taking metformin (MET) and SU when initiating insulin. Among the 22, 418 MET/SU patients, 31% discontinued SU within 3 months of insulin initiation and, by 12 months, 55% had discontinued SU. Sulfonylurea discontinuation was similar among many patient and provider characteristics, while being modestly positively associated ( p < .05; HRs <1.5) with female gender, more co-morbidities, cardiac revascularization, chronic liver disease, hospitalizations with a T2DM diagnosis, and hypoglycemia prior to insulin initiation. SU discontinuation was modestly inversely associated with receiving an insulin prescription from an endocrinologist (HR = 0.90, 95% CI = 0.85–0.95). Conclusions: Roughly half of commercially-insured T2DM patients discontinued SU within 1 year after insulin initiation, and SU discontinuation was not strongly associated with a range of patient and provider characteristics.